Family Welfare Empowerment (PKK) of Ban Village Karangasem through Product Development Based on Roselle and Mangoes - Suriati, Luh; Nazir, Novizar; Azmi, AFMN; Zamri, SFM; Singapurwa, NMAS; Semariyani, AAM; Mangku, IGP; Sudiarta, IW; Candra, IP; Setianingsih, NPP; Putra, IPAR; Pratiwi, NLPYM; Mulia, IKOB; Kusuma, DAJ; Winduyasa, IW; Prastiawan, IBO; Girindra, AANS (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Community empowerment through the development of roselle and mango-based food products in Ban Village, Karangasem, Bali, aims to enhance community independence and welfare by developing roselle and mango-based food products in Ban Village, Karangasem, Bali. The focus is on effective food processing, fostering entrepreneurial spirit, and providing training in product diversification and marketing. Collaboration with universities and networks supports sustainable development, increases the economic value of local agricultural products, opens new market opportunities, and encourages sustainable ecotourism while preserving local wisdom in Ban Village. The initiative involves 15 members of the Ban Village PKK group, established in 2010. The implementation method is structured and includes coaching, training, mentoring, and consultation to address various challenges in adding value for partners. Community service activities are conducted through lectures, discussions, demonstrations, training sessions, and Q&A. As a result, the community empowerment activities significantly increased the knowledge and skills of PKK members in processing and marketing roselle and mango products, such as roselle tea and mango dodol, thereby creating new sources of income. Despite the progress, most participants require further training in packaging and product variety. Diversification efforts have increased the economic value of local agricultural products, providing stable profits for farmers.